Suffering Job Insecurity: Will the Employees Take the Proactive Behavior or Not? - Yao, Xun; Li, Meng; Zhang, Huiqin (Frontiers in Psychology, 2021)
Job insecurity is considered an important antecedent of an employee’s creativity. Though, the relationship between job insecurity and proactive behavior has been neglected in previous human resources management study. The aim of this study is to explore the influence of job insecurity on employees' proactive behavior and its mechanism. Based on the social cognitive theory and cognitive appraisal theory, two type of cognitive appraisal of employee’s job insecurity (hindrance vs. challenge) as mediator variables of job insecurity and proactive behavior association. In addition, the moderator roles of self-efficacy is examined. This study is carried out with 257 employees from Chinese firms to examine the hypothesized moderated mediation model by using the hierarchical regression analysis and the bootstrap. The results showed a different effect of job insecurity depending on its conceptualization. The results shows that job insecurity has a negative effect on employees' proactive behavior. At the same time, cognitive appraisal of employees’ job insecurity mediated the association between job insecurity and employee’s proactive behavior. Self-efficacy not only moderate the relationship between job insecurity and cognitive appraisal but also moderate the cognitive appraisal’s mediation effect between job insecurity and proactive behavior. The study’s theoretical and practical contributions and future research are discussed.